PENGARUH PUBLISITAS, KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA CYCLO COFFEE & APPAREL - Novia Anggraini; Parlagutan Silitonga (Eduturisma, 2019)
This research aims to analyze the impact of publicity, product quality, and price on customer loyality at Cyclo Coffee & Apparel. The population are buyers at Cyclo Coffee & Apparel. Samples were taken of 100 respondens by accidental sampling technique. Data were collected after quantitive. The quantitive analysis by classic assumption test (normality test, multicollinearity test, heteroscedasticity test and linierity test), then by multiple regression. While hypotheses testing by the F test and t-test, and analysis correlations and determination (R2). The results found that Publicity, Product Quality, and Price have affected Customer Loyality (Y), significantly both by partially and simultaneously.